RELATIONAL MARKETING ANALYSIS OF CUSTOMER LOYALTY OF “RUMAH ADAT BUGIS” IN SIDENRENG RAPPANG REGENCY - Hasanuddin, Muhlis; Ramlan, Pratiwi; L, Syahrir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of relational marketing on customer loyalty for the